"n Herdefiniëring van Paulus se konflik in Galasië: Die brief aan die Galasiërs deur die bril van die sosiale wetenskappe - Craffert, P. F. (Hervormde teologiese studies, 1994)
Redefining Paul’s conflict in Galatia: The letter to the Galatians through the lense of the social sciences Traditional attempts at identifying Paul’s oppponents in the letter to the Galatians are methodologically stamped by a history-of-ideas approach; this is accompanied by at least two interpretive traditions (one focusing on the Reformation question of righteousness by works or by faith, and the second by the inclusion of Gentiles in the people of God). After a social- scientific methodology is introduced, three facets of Paul’s social realities are discussed: communication in a predominantly oral culture, Judaism as a first-century religious phenomenon, and the household institution. It is suggested that these provide us with an opportunity for redefining the conflict as a conflict on Paul’s honour and authority.